Determinants of Muslim Family Financial Planning - Arief Hidayat Tumanggor; Muhammad Salman; Reza Febrian; Sugianto Sugianto (International Journal Of Economics Social And Technology, 2022)
Family financial planning is a systematic, thorough, and planned process to identify and analyze needs and investigate one's goals to achieve family financial goals in the short, medium, and long term, very important for achieving family welfare. The basic values of Islam that are needed as a guide in planning family finances First All property, whether owned by objects, soul and body in the truth, belongs to Allah, and will surely return to Allah, the position of man is security for the trust given by Allah. The Second Human is made by God as the Caliph (Deputy) of God on earth, in utilizing natural resources for human life that is decent, civilized, and carried out in a just manner. third, the struggle for wealth does not have to sacrifice religious duties and obligations. Because humans were created to worship God and life is a test to eternal life.